Pengaruh Impulse Buying, Kualitas Produk dan E-WOM Terhadap Keputusan Pembelian Album Musik K-pop Secara Online (Studi Kasus Pada Fanbase Treasure Maker Indonesia) - Qolbi, Syafira Naurin; Priyono, Achmad Agus; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to analyze the effects of Impulse Buying, Product Quality and E-WOM on the purchase of K-pop music albums by online. This research uses explanatory research with a quantitative approach. The data sources of this reseacrh are primary data from questionnaire distribution to treasure maker fanbase at onlycsuyon_shop and secondary data from documents, journals, previous researchers and other. The population used in the research is unknown. Therefore, the sampling technique in this research used maholtra formula and purposive sampling wich obtained a total of 95 samples with a questionnaire distribution method using a likert scale. The data were analyzed using multiple linear regression measured using SPSS. Test the hypothesis using the t-test and F-test. The result show that Impulse Buying, Product Quality and E-WOM had a simultaneously effects on purchasing decisions. Impulse Buying partly has a positive and significant on purchasing decisions. Product Quality partly has a positive and significant on purchasing decisions. Meanwhile, E-WOM doesn’t have a positive and significant effect on purchasing decisions. Keywords: Impulse Buying, Product Quality, E-wom and Purchasing Decisions